Intermediate layer formation between inclusion and matrix during synthesis of unidirectional fibrous composite; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Knyazeva A. G. Anna Georgievna; Kruykova O. N. Olga; Lurie S. A. Sergey; Solyaev Yu. O. Yury; Shavnev A. A. Andrey (2014, 2014)
Title screen